Tuning the product distribution during the catalytic pyrolysis of waste tires: The effect of the nature of metals and the reaction temperature - Osorio Vargas, Paula Alejandra (2021)
Metal catalysts based on Ni, Co, and Pd supported on SiO2 were evaluated in the catalytic pyrolysis of waste tires using pyrolysis experiments coupled to gas chromatography/mass spectrometry (Py–GC/MS) and thermogravimetric analysis coupled with Fourier Transform Infrared spectrometer (TGA–FTIR) techniques. The effect of temperature and the nature of metals on the product distribution and reaction pathways was determined. Catalytic pyrolysis promoted aromatization and cracking reactions at particularly low temperatures ca. 350 °C, leading mainly to the formation of alkenes (isoprene), aromatic terpenes (p-cymene), aliphatic terpenes (d,l-limonene), and other aromatic compounds such as benzene, toluene, and xylenes (BTX). The Pd/SiO2 catalyst was the most selective toward aromatic compounds (around 40 %), owing to its well-known hydrogenation/dehydrogenation capacity, while CCsingle bond bond cleavage reactions, leading to alkenes, were more favored on the Ni/SiO2 and Co/SiO2 catalysts. In all cases, high selectivity to limonene and isoprene was observed at low temperature. Above 400 °C, no significant differences in product distribution were observed between catalyzed and uncatalyzed pyrolysis. Herein, selectivity toward high-value hydrocarbons (i.e., d,l-limonene, isoprene, BTX, and p-cymene) during the catalytic pyrolysis of waste tires was tuned by the nature of the supported transition metals (i.e., Ni, Co, Pd) and the reaction temperature (e.g., <400 °C). The results demonstrate that the use of these catalysts is a promising strategy to valorize waste tires into high added-value products.